Evaluation on dynamic change and interrelations of ecosystem services in a typical mountain-oasis-desert region. (October 2018) - Wei, Hejie; Xu, Zihan; Liu, Huiming; Ren, Jiahui; Fan, Weiguo; Lu, Nachuan; Dong, Xiaobin
Highlights: Provisioning services have improved, but supporting services was declining in the Manas River Basin. Large-scale reclamation and population growth were the main factors in most ecosystem services (ES) changes. Synergies or tradeoffs between provisioning and regulating services may change under the influence of policies. Intensified human activities caused the tradeoffs between supporting services and provisioning or regulating services. It is necessary to integrate ES into environmental policy management platform in the Manas River Basin. Abstract: Investigating the historical dynamics, interactions and driving factors of multiple ecosystem services (ES) is crucial to realize ES sustainability. The mountain-oasis-desert system (MODS) is a coupled socio-ecological system, and the Manas River Basin is a typical representative of the MODS and faces a sharp conflict between socioeconomic development and ecological conservation. Based on historical documents, meteorological data, hydrological data and remote sensing data, we identified long temporal variations (approximately 60 years) and relationships of eight ES in the study area. A gray relational analysis (GRA) was applied to quantify the influence of climate and anthropogenic factors on eight ES. The results showed, since the large-scale reclamation of the study area in 1949, that the provisioning services (i.e., grain, cotton and livestock) and most regulating services (i.e., sandstorm control and climate regulation) improved markedly, but the supporting services (i.e., soil conservation and habitats) had declined. The linear fit charts indicated the synergies between the provisioning services and most regulating services but tradeoffs between provisioning services and supporting services (especially the habitats service). The dramatic population growth and intensified human activities (e.g., large-scale reclamation and the deforestation) were the main drivers of most ES, while climate fluctuation (e.g., temperature and strong wind days) was the main factor affecting certain regulating services (e.g., hydrological regulation and sandstorm control). The declines in supporting services and ES tradeoffs caused by the intensified human activities threatened the sustainability of other ES and should attract close attention. Investigating the ES historical dynamic in the Manas River Basin can help us further understand the socio-ecological system development of the typical mountain-oasis-desert region and provide valuable information for ES management.